Understanding fans’ reactions to sponsorship in the Saudi pro league: Effects of sponsor type and integration cues - Alenazi, Sultan Alaswad (Edelweiss Applied Science and Technology, 2025)
This research comprises two complementary studies examining how fans evaluate sponsorships in the Saudi Professional League (SPL). Study 1 employed a quantitative survey (n = 563/600, 93.8% response rate) to investigate how processing fluency and perceived fan benefits influence fans’ evaluation of sponsorships. Both variables positively affected fan attitudes toward sponsors. Building on these findings, Study 2 utilized a 2 × 2 between-subjects experimental design (n = 374) to examine how sponsorship type (naming rights vs. jersey sponsorship) and integration level (high vs. low) influence fan responses. The results indicated that naming rights (vs. jersey) sponsorships generated higher processing fluency and perceived fan benefits, while high integration cues further reduced these effects. Collectively, the two studies demonstrate that fans interpret sponsorships through both cognitive ease and relational value, showing that integrated, long-term partnerships foster stronger, more favorable attitudes toward sponsors within the Saudi sports context. For practitioners, the findings suggest that SPL sponsors should prioritize arrangements that are easy for fans to process while contributing meaningfully to the fan experience.